Multiliteracy Approaches to Teaching Social Empathy and Justice through A.A. Navis’s Literary Works in Elementary Education - Manurung, Rosida Tiurma; M. P., Destalya Anggraini (International Conference on Elementary Education, 2025)
This study explores how multiliteracy pedagogy using A.A. Navis’s literary works fosters social empathy, promotes gender equality, and enhances moral awareness among elementary students in Bandung, Indonesia. Objective: To examine the role of local literaturein enhancing students’ emotional and social literacy through empirical classroom-based learning. Method: A qualitative descriptive design was applied, including classroom observations, student reflection journals, and teacher interviews involving 34 fifth-gradestudents and 2 teachers. Findings: The results indicate that multiliteracy-based learning improved students’ emotional expression, cooperation, and moral reasoning. Students related characters such as “Mother” and “Sutan Duano” to acts of empathy and fairness, while teachers observed increased collaboration and reduced classroom conflict. Conclusion: Integrating multiliteracy pedagogy with Indonesian local literature serves as an effective model to cultivate empathy, inclusivity, and character-based education aligned with Sustainable Development Goals (SDG) 4 and 5.